Distribution of 137Cs in the brown hare’s body, at the territory of various radioactive pollution - A. V. Gulakov (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2009)
The long-term data on accumulation and distribution of the radionuclide 137Cs in an organism of the brown hare obtained from the territories of various levels of radioactive pollution are presented. Essential fluctuations of the radionuclide content in the hare’s organs and tissues are shown. Results of the research have an important practical value for the hunting facilities at the radioactive polluted territories.